A Study on The Significant Role Of Stakeholders In Implementing Adip Schemes for Students With Intellectual Disabilities in an Inclusive Classroom Settings - Fr. Baiju Thomas (Universitas Negeri Makassar, 2021)
The current research study is explores on the key role of Stakeholders in implementing ADIP (Assistance to Disabled Persons for purchase / Fitting of Aids / Appliances) schemes for students with intellectual disabilities (SwIDs) in an inclusive classroom settings in the Thriuvandathpuram district of Kerala. This scheme is designed to help needy disabled people obtain enduring, complex, and technically built current, standardized aids and appliances in order to facilitate physical, emotional, and psychological rehabilitation of SwIDs while also increasing their growth opportunities. SwIDs are given assistive equipment with the goal of improving their independent living and preventing secondary impairment. The scheme's aids and equipment must be certified in order to be used. The ADIP schemes are the government of India's main program that strives to provide academic aid to disabled persons in order to help them with overall societal, financial, and occupational development. When SwIDs fulfill the required entry criteria, they may be eligible for an ADIP scholarship for living independently. Inclusion promotes for all students, regardless of sex, physical, academic, social, financial, mental, cultural, or other features, to be sought out, welcomed, nurtured, respected, and educated in classrooms. The full inclusion of students with and without special needs into the same classes and schools, make known to everybody to the very same teaching strategies, is known as IE. A total of 32 general educators, 20 special educators and parents 54 were chosen for the present research study. The study makes use descriptive survey method to investigate on the significant role of stakeholders in implementing ADIP schemes for SwIDs. The study sampled 25 schools using a random sampling technique. The data was analyzed quantitatively, and the findings were tallied using percentage. To improve reliability, the findings were recorded with participants. The findings have a significant effect on the confidence of these stakeholders, but it also challenges the aim of guaranteeing that ADIP schemes are implemented in accordance with the government reforms in inclusive classroom settings in the Thriuvandathpuram district of Kerala.